2018
DOI: 10.1159/000481097
|View full text |Cite
|
Sign up to set email alerts
|

Is Surgical Excision Necessary in Breast Papillomas 10 mm or Smaller at Core Biopsy

Abstract: Background: The objective of this study was to propose managements for breast papillomas of 10 mm or smaller initially diagnosed at core biopsy. Method: We reviewed the data of patients in our center from 2004 to 2013. 116 lesions of 10 mm or smaller as measured by ultrasound (US) were diagnosed as papillomas at core needle biopsy (CNB) or vacuum-assisted biopsy (VAB). 74 of the papillomas diagnosed by CNB were surgically excised, the others were followed by imaging surveillance. Result: 13 of 116 lesions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
2
7
1
1
Order By: Relevance
“…In our cohort, papillary lesions without atypia had an overall upgrade rate of 4.72%, which is consistent with recent international series which report overall upgrade rates of 2.3–7% 8–10 . Of these lesions, those larger than 8 mm demonstrated a higher upgrade rate (13.63%) than those smaller than 8 mm (0%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our cohort, papillary lesions without atypia had an overall upgrade rate of 4.72%, which is consistent with recent international series which report overall upgrade rates of 2.3–7% 8–10 . Of these lesions, those larger than 8 mm demonstrated a higher upgrade rate (13.63%) than those smaller than 8 mm (0%).…”
Section: Discussionsupporting
confidence: 91%
“…[5][6][7] In our cohort, papillary lesions without atypia had an overall upgrade rate of 4.72%, which is consistent with recent international series which report overall upgrade rates of 2.3-7%. [8][9][10] Of these lesions, those larger than 8 mm demonstrated a higher upgrade rate (13.63%) than those smaller than 8 mm (0%). A similar finding was reported by Yu et al, who found that papillary lesions larger than 15 mm, regardless of whether atypia was present, have a statistically significant increased risk of malignancy on excision.…”
Section: Discussionmentioning
confidence: 99%
“…50%No association with age and size lesionKo et al 2017 [63] n = 346 PL in CNBUpgradeIn VAB ( n = 211)In OE ( n = 135)UpgradeOverall in 2.3%If size < 1cm: 0.9%Size of PL correlates with upgradeClose follow-up with ultrasound instead of excisionMoon et al 2016 [64] n = 65 PL in CNBUpgradeIn VAB ( n = 12)In OE ( n = 53)UpgradeIn OE in 9% (5/53)In VAB 8% (1/12)No recommendationNiinikoski et al 2018 [65] n = 80 PL in CNBSmall PL in selected patients-OE can be avoidedPareja et al. 2016 [66]Upgrade in OE ( n = 171) after PL Without atypiaIn CNBUpgradeIn OE 2.3% (4/171)Regardless of size, observation is appropriate at radiologic–pathologic concordant CNBSeely et al 2017 [67] n = 107 PL in OEUpgrade afterVAB ( n = 60)CNB ( n = 47)Upgrade in OEAfter VAB in 1.6% (1/60)After CNB in 8.5% (4/47)Higher upgrade in OE if PL is diagnosed on CNBTatarian et al 2016 [68] n = 16 PL in CNBUpgrade in OEUpgrade in OEIn 2/16 cases (12.5%)Surgical excision should be considered in patients with benign papillomasTran et al 2017 [69] n = 43 PL in CNBUpgrade in OEUpgrade in OEIn 1/43 cases (2%)Low-upgrade rate in OEWyss et al 2014 [70] n = 156 PL in CNBUpgradeIn VAB ( n = 135) andFollow-up ( n = 21)(Median 3.5 years)Upgrade after follow-up1.2% (2/156)VAB is recommended as the method of choice for removal of PLYamaguchi et al 2015 [71] n = 142 PLFollow-up imagingAfter VAB ( n = 125)After CNB ( n = 17)Upgrade in OE ( n = 17)4/17Discordant lesions should undergo OEYang et al 2018 [72] n = 116 PL(On CNB or VAB)10 mm or smallerOE n = 74Surveillance n = 42Overall upgrade 11% (13/116)Upgrade after VAB (0%)Upgrade after CNB (16.5%)Higher upgrade in OE-After CNB-Older age-Pl with atypia…”
Section: Resultsmentioning
confidence: 99%
“…Surgical management of intraductal papilloma diagnosed on core biopsy is controversial. Some authors have suggested that intraductal papilloma greater than five millimetres should be excised [9]. In our study, the majority of intraductal papillomas were less than five centimetres (52.5%), and more than 90% were solitary.…”
Section: H and E Hematoxylin And Eosinsupporting
confidence: 46%